Reaction of N-(Per-O-acetyl-β-D-glucopyranosyl)-Nʼ-(4ʼ,6ʼ-diarylpyrimidine-2ʼ-yl)thioureas with Ethyl Bromoacetate - Nguyen Dinh Thanh (E-Journal of Chemistry, 2011)
Some new 2-iminothiazolidin-4-ones having pyrimidine ring have been synthesized by reaction of substituted N-(per-O-acetyl-β-D-glucopyranosyl)-Nʼ-(4ʼ,6ʼ-diarylpyrimidine-2ʼ-yl)thioureas with ethyl bromoacetate. The structure of isomeric products has been confirmed by spectroscopic methods, such as IR, 1H and 13C NMR.